Information Systems Modeling and Design - Nguyen, Dinh Van (Khoa Quốc tế, ĐHQGHN, 2020)
This course promotes student's knowledge and understanding of the process of developing information systems; develops an understanding of various approaches in developing information systems; provides the students with the knowledge of various techniques and tools used in the process of information systems planning and requirements analysis; develops skills in certain fundamental techniques of information systems planning and analysis.